The Effect of Job Description on Employee Performance of Omani Public Sector: Mediating Role of Organizational Justice - AL Rawas, Shahab Ahmed Salim Mubarak; Jantan, Mohd Dan (Technium Business and Management, 2022)
Employee performance (EP) is critical for organizations and individuals. Prior literature focused on EP in the context of the private sector while few examined EP in the context of the public sector in emerging economies. The purpose of this study is to examine the effect of the job description (JD) on organizational justice (OJ) and EP in the context of public sector organizations in Oman. The population of this study includes five ministries in Oman. A stratified random sampling was deployed. A total of 420 public sector employees participated in this study. The findings showed that JD affected positively the EP and OJ. In addition, OJ has a positive impact on EP and mediated the effect of JD on EP. A clear and specified JD helps in improving the OJ and EP while establishing a culture of justice will positively lead to a better EP and enhance the explanation of the relationship between JD and EP. Decision makers are recommended to create clear JD and to improve the OJ to increase the EP of employees in the public sector.